Cancer Treatment and Immunotherapy during Pregnancy - Antonios Koutras; Thomas Ntounis; Zacharias Fasoulakis; Theodoros Papalios; Savia Pittokopitou; Ioannis Prokopakis; Athanasios Syllaios; Asimina Valsamaki; Athanasios Chionis; Panagiotis Symeonidis; Athina A. Samara; Athanasios Pagkalos; et al. (MDPI AG, 2022)
Background/aim: Immunotherapy has, in recent years, witnessed an expansion in its indications for the treatment of cancer. Coupled with the fact that, nowadays, even more women choose to postpone parenthood, thus increasing their chances of having some kind of malignancy during pregnancy, more and more women are eligible for receiving immunotherapy during this period of their lives. The cases of cancer diagnosed during pregnancy is an ever-increasing trend nowadays. Materials and methods: The oncologists and clinicians treating women often face a range of ethical and therapeutic dilemmas due to the particularity of the patient's conditions. The primary concern is the protection of the mother, firstly, and then the fetus (through adjustments to the various treatment regimens) if possible. Results and conclusions: Oncological drugs, radiation therapy, surgery, or a combination of all the above methods are selected, depending on the case. In this project, we studied the oncology drugs used for various types of gestational cancer, their appropriateness and timing, as well as their possible effects on the parent and embryo upon their administration. Various studies have shown that the administration of oncological drugs should be postponed until at least after the first trimester of pregnancy.